Biochemical Marker for Menkes Disease - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1993)
Plasma and CSF levels of catechols in 10 patients with Menkes disease, ranging in age from 9 days to 27 months, were compared with control groups and patients with congenital absence of dopamine-B-hydroxylase (DBH) at the National Institutes of Health, Bethesda, MD.